Risk of recurrent laryngeal nerve palsy in patients undergoing thyroidectomy with and without intraoperative nerve monitoring. Issue 13 (18th August 2016) - Bergenfelz, A.; Salem, A. F.; Jacobsson, H.; Nordenström, E.; Almquist, M.; ,
Abstract: Background: Vocal cord palsy occurs in 3–5 per cent of patients after thyroidectomy. To reduce this complication, intraoperative nerve monitoring (IONM) has been introduced, although its use remains controversial. This study investigated the risk of postoperative vocal cord palsy with and without the use of intermittent IONM. Methods: Patients registered in the Scandinavian Quality Register for Thyroid, Parathyroid and Adrenal Surgery, 2009–2013, were included. Early palsy of the recurrent laryngeal nerve was diagnosed within 6 weeks after surgery. Permanent palsy was defined as that persisting after 6 months. Univariable and multivariable logistic regression analyses were used to examine risk factors for vocal cord palsy. Results: The cohort consisted of 5252 patients undergoing thyroidectomy. IONM was used in 3277 operations (62·4 per cent); postoperative laryngoscopy was performed in 1757 patients (33·5 per cent). Early vocal cord palsy occurred in 217 patients (4·1 per cent), of which three were bilateral, all in the group without IONM. Permanent vocal cord palsy occurred in 62 patients (1·2 per cent). In the multivariable analysis of 1757 patients who had postoperative laryngoscopy, the use of IONM was not associated with a decreased risk of early vocal cord palsy (odds ratio (OR) 0·67, 95 per cent c.i. 0·44 to 1·01), but decreased the risk of permanent vocal cord palsy (OR 0·43, 0·19 to 0·93). [Correction added on 11 November 2016 after first publication: the word 'routine' has been removed from this section.] Conclusion: IONM reduced the risk of permanent vocal cord palsy. No bilateral recurrent laryngeal nerve injury occurred following IONM. Abstract : More evidence of benefit